Study of antioxidant activity of non-conventional Brazilian fruits - Luzia, D. M M [UNESP]; Jorge, N. [UNESP] (Springer Nature, 2011)
This study aimed to analyze the proximate composition of seeds from some non-conventional Brazilian fruits, as well as to evaluate the antioxidant activity through DPPH • free radical and to quantify the total phenolic compounds. To obtain the extracts, dried and crushed seeds were extracted with ethanol for 30 min, in a ratio of 1:3 (seeds:ethyl alcohol), under continuous agitation, at room temperature. Then, the mixtures were filtered and the supernatants were subjected to rotary evaporator under pressure reduced to 40 °C. The results report that the seeds of non-conventional fruits are remarkable sources of lipids, and the extraction of oil from these seeds could be an alternative for the commercial utilization of waste. They also presented significant percentages of protein and carbohydrates. Ethanol extracts of seeds from non-conventional Brazilian fruits showed relevant antioxidant activity and high amount of phenolic compounds. Therefore Brazilian non-conventional fruits can be used as functional food products or feed. © 2011 Association of Food Scientists & Technologists (India).
Keywords: DPPH •; Extracts; Fruit; Seeds; Total phenolic compounds